Integration of medical imaging including ultrasound into a new clinical anatomy curriculum. Issue 3 (6th August 2014) - Moscova, Michelle; Bryce, Deborah A.; Sindhusake, Doungkamol; Young, Noel
<x xml:space="preserve">Abstract</x> In 2008 a new clinical anatomy curriculum with integrated medical imaging component was introduced into the University of Sydney Medical Program. Medical imaging used for teaching the new curriculum included normal radiography, MRI, CT scans, and ultrasound imaging. These techniques were incorporated into teaching over the first two years of the program as a part of anatomy practical sessions, in addition to dedicated lectures and tutorials given by imaging specialists. Surveys were conducted between 2009 and 2012 to evaluate the student acceptance of the integration. Students were asked to rate individual activities as well as provide open‐ended comments. The number of students who responded to the surveys varied from 40% to 98%. Over 90% of the respondents were satisfied with the overall quality of teaching in the anatomy units. In summary, 48% to 63% of the responding students thought that the specialist imaging lectures helped them learn effectively; 72% to 77% of students thought that the cross‐sectional practical sessions helped them to better understand the imaging modalities of CT, MRI, and ultrasound; 76% to 80% of students considered hands‐on ultrasound session to be useful in understanding the application of ultrasound in abdominal imaging. The results also revealed key similarities and differences in student perceptions of the new integrated curriculum for students with both a high and low prior exposure to anatomy. Further evaluation will aid in refining the integrated medical imaging program and providing its future direction. Anat Sci Educ 8: 205–220. © 2014 American Association of Anatomists.